The Performance Identity of Electric Bass by Stuart Hamm’s Slapping and Tapping Techniques - Khaohan, Bophit (Journal of Fine and Applied Arts Khon Kaen University, 2023)
The purpose of this research was to study the performance identity of electric bass by Stuart Hamm’s slapping and tapping techniques. The study aimed at finding out the identity of electric bass performance with the techniques of Stuart Hamm’s slapping and tapping based on the concept of slapping and tapping techniques classification by Stuart Clayton and Chad Johnson was used for data analysis was analyzed using a qualitative research method in the manner of documentary research from primary and secondary sources. This study focuses on the analysis for 5 pieces on the electric bass instrumental music of Stuart Hamm on the slapping and tapping techniques. The results of the study were as follows: Black Ice, Count Zero, and If You Scared, Stay Home! It has a variety of slapping and tapping with 5 techniques. The pieces that were used in the second-order were The Hummer and Lone Star, with 4 techniques. It was also found that Stuart Hamm had a unique identity for using a combination of slapping and tapping techniques in electric bass. Besides, secondary identities include techniques including left-hand slap and sixteen note lines, Double Stop, Arpeggio Seventh Chords Tapping, and Scale Fragment Tapping. The least used techniques include Strumming, Double Popping, Flamenco – Raking, and Accompaniment Power Chord Tapping.